Strategic Impact of IFRS Adoption on Financial Transparency and Institutional Performance: Evidence from the Palestinian Banking Sector - Fayez Lotfi Dweikat; Nehad Ibrahim Abd Alfatah Ineizeh; Nur Hidayah Laili; Muhammad Iqmal Hisham Kamaruddin (Academic Hosting & Event Management Solutions, 2026)
Indexed by (Tier 2)